Films to support Aboriginal and multicultural education programs - McIntosh, J. (Joyce); New South Wales. Multicultural Education Centre ([Sydney] : N.S.W. Dept. of Education, Directorate of Special Programs, Multicultural Education Centre, 1981)
Includes films to support ESL programs; gives summary and distribution, length and other details.
Keywords: Ethnic minorities. Social adjustment. Australia. Filmographies. For teaching; Minorities -- Australia -- Film catalogs; Education - Indigenous studies; Language - Bilingualism and multilingualism - English as a second language; Education - Language - Indigenous languages; Education - Skills and curriculum - Cultural awareness; Settlement and contacts - Ethnic groups, immigration and multiculturalism; Australia